From gender stereotyping to constructing political identity: changes in Malaysiakini’s portrayal of women candidates during Malaysia’s 2008 and 2013 general elections - Usha Devi Rajaratnam,; Antoon De Rycker, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The under- and misrepresentation of women politicians and electoral candidates in the news media has been well documented. Much less is known, however, about how news providers portray women politicians differently over time, either in tandem with developments in the political and media landscape — e.g., the presence, visibility, and role of women in politics — or to reflect changes in internal newsroom policies. Against this background, this study aims to compare and contrast the news coverage of female candidates in two successive general elections, using multiethnic Malaysia as its case. Samples of news articles from Malaysiakini — one of Malaysia’s major independent online newspapers — were collected for the election periods of 2008 and 2013 and subjected to qualitative content analysis, with a focus on headlines. Findings suggest that the more recent reporting of women candidates helps position women as competent professionals compared with the more gendered portrayals five years before. At the same time, there is a trend away from descriptive to interpretive journalism, putting the many challenges that Malaysian women face as candidates in a wider societal and international context. The implications of the study are that also in Malaysia, individual newspapers can change over time, revise their gender stereotypes and overall play a stronger role in enhancing women’s electoral viability.